The Application of Borehole Hydrophone Arrays in Hardrock Environments - Greenwood, Andrew; Urosevic, Milovan; Dupuis, Christian; Kepic, Anton (EAGE, 2014)
The geometry of a VSP survey allows us to understand the characteristics of both the transmitted and reflected wavefields. As such, VSP is an “in-field seismic laboratory”, necessary for understanding the origin of seismic events. VSP enables calibration of surface reflection images and the survey can be designed to produce an image around the borehole at a much higher resolution than the surface reflection method. The main drawback of the method with respect to the mining community is the high logistic cost. Hence the main objective of the research presented here is to look into alternative ways of implementing VSP surveys that are cost effective, readily implementable in slim holes and pose lower risk to equipment in unstable uncased mineral exploration boreholes. As shown in this work, these objectives have been met using a borehole hydrophone array. Presented are two field trials in the Agnew-Wiluna and Kambalda regions of Western Australia. The results of these field experiments demonstrate that a borehole hydrophone array is capable of imaging structure in a complex geologic environment. These results, however, are not easily achieved because of the high sensitivity of hydrophones to acoustic modes in the borehole and the passive coupling to the formation.